A review of major rare earth element and yttrium deposits in China. Issue 1 (2nd January 2022) - Yin, J. N.; Song, X.
Abstract: Rare earth element and yttrium (REY) deposits are important strategic resources widely used in high-tech applications, such as solar cells and wind turbines. This paper summarises the temporal-spatial characteristics and genesis of REY deposits in China classified as alkaline carbonatite, ion-adsorption, placer, sedimentary metamorphism, marine sedimentary phosphorite and coal-hosted REY types. This study focuses on alkaline carbonatite and ion-adsorption deposits, because of their importance in terms of both exploitation and global reserves. The general characteristics, genesis, and enrichment of these REY deposit types are summarised, and eight districts have been identified as having prospectivity for REY, based on geological and geochemical data. An overview of these districts is presented, together with a detailed investigation of four important districts in terms of geological settings, mineralisation, regional deposit models and metallogenic prospect. KEY POINTS: REY deposits in China can be classified as alkaline carbonatite, ion-adsorption, placer, sedimentary metamorphism and marine sedimentary phosphorite and coal-hosted REY types. Ion-adsorption REY in the weathering profile of granitic rocks is strongly controlled by the resistance to weathering, climate, topography and layers of weathering crust. Carbonatite and alkaline rocks are major hosts for REYs and commonly have high concentrations of REY-bearing accessory minerals. Eight districts have been identified as having prospectivity for REY in China.